Early Embryonic Expression of Murine Coagulation System Components - Ong, Kelly; Horsfall, Wendy; Conway, Edward M.; Schuh, Andre C. (Thrombosis and Haemostasis, 2000)
The development of the embryonic coagulation system, and its contribution to the maintenance of vascular integrity during the formation of embryonic blood vessels, remain poorly understood. We have characterized the temporal expression patterns of 27 hemostasis-related genes during murine development. We show that, although most coagulation and fibrinolysis-related factors are expressed coordinately b 7.5 dpc, several, including FIX, FXII and PAI2, are not detectable until later developmental timepoints. The expression of hemostasis-specific genes prior to the formation of a functional circulatory system supports the view that some coagulation factors have additional non-hemostatic functions during development. In addition, the discordant expression of some factors suggests that the embryonic hemostatic system may be distinct from that of the adult. These analyses will help to elucidate the regulation of hemostasis during embryonic/vascular development, and will provide a framework to facilitate the interpretation of gene inactivation studies.
Keywords: Embryo; hemostasis; vascular development; knock-out